2012
DOI: 10.1016/j.jpainsymman.2011.09.006
|View full text |Cite
|
Sign up to set email alerts
|

The Experiences of Relatives With the Practice of Palliative Sedation: A Systematic Review

Abstract: Relatives' experiences with palliative sedation are mainly studied from the perspective of proxies, mostly professional caregivers. The majority of relatives seems to be comfortable with the use of palliative sedation; however, they may experience substantial distress by the use of sedation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
50
1
20

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
4

Relationship

2
8

Authors

Journals

citations
Cited by 65 publications
(74 citation statements)
references
References 52 publications
3
50
1
20
Order By: Relevance
“…26 The questionnaire was piloted in three interviews. This led to some small changes in the formulation of the questions.…”
Section: Methodsmentioning
confidence: 99%
“…26 The questionnaire was piloted in three interviews. This led to some small changes in the formulation of the questions.…”
Section: Methodsmentioning
confidence: 99%
“…Family members may experience significant distress when their relative is receiving continuous palliative sedation (117). They may need reassurance that the sedated patient is no longer distressed (93).…”
Section: Addressing Ongoing Communication and Other Concerns During Pmentioning
confidence: 99%
“…Most of these relatives have been found to be comfortable with the use of palliative sedation, although some had experienced substantial distress. 23 Furthermore, changing the life expectancy of the patient from <1 week into <1 month resulted in a small but significant decrease in the level of agreement with the physician's act of providing sedation. The interviews revealed that the patient's e680 British Journal of General Practice, October 2013 wishes and suffering are more important aspects when considering the acceptability of palliative sedation than the patient's life expectancy and whether or not palliative sedation was provided with the goal of hastening death.…”
Section: Comparison With Existing Literaturementioning
confidence: 99%